Evaluation of ureteral lesions in ureterorenoscopy: impact of access sheath use. (4th March 2018) - Lildal, Søren Kissow; Andreassen, Kim Hovgaard; Jung, Helene; Pedersen, Malene Roland; Osther, Palle Jörn Sloth
Abstract: Objective: The aim of this study was to evaluate the incidence of ureteral lesions in retrograde intrarenal surgery (RIRS) with and without the use of a 10/12 Fr ureteral access sheath (UAS). A further objective was to search for preoperative factors that could influence the risk of ureteral damage. Materials and methods: Data were collected from a clinical database on 180 consecutive adult patients undergoing RIRS for kidney stones with or without a 10/12 Fr UAS. The primary outcome measure was ureteral lesions endoscopically identified at the end of surgery using the Post-Ureteroscopic Lesion Scale (PULS) classification system. Results: The use of 10/12 Fr UASs resulted in less severe lesions than reported previously with larger diameter UASs. There was a higher risk of superficial lesions in the UAS group, with a calculated crude odds ratio (OR) of 1.84 [95% confidence interval (CI) 1.00–3.37]. When adjusting for age and gender, the OR was 1.68 (95% CI 0.90–3.13; p  = 0.10) and thus was not significant. The only factor that remained significant was age (OR =1.02/year, 95% CI 1.00–1.04). Conclusion: There was a trend towards a higher risk of ureteral lesions in RIRS with a 10/12 Fr UAS compared with an endoscope alone, but when adjusting for age and gender the incidence of ureteral lesions was comparable between RIRS with and without the use of a 10/12 Fr UAS.